The Role of Ischemia-modified Albumin and Ischemia-modified Albumin to Albumin Ratios in Patients with Alopecia Areata - TanaCan, Efsun; Oztekin , Aynure; Savcı, Unsal; Senel, Engin; Oztekin, Coskun; Neseoglu, Salim; Ozcan, Erel (Dermatology Practical & Conceptual, 2023)
Objective: To investigate the role of ischemia-modified albumin (IMA) and IMA/albumin levels in patients with AA. Methods: The present prospective crossectional study includes patients ≥ 18 who admitted to the Dermatology and Venerology Department of XXXX University Hospital between April 1 2021, and September 30 2021. 70 patients participated in the study (n=34 for the study group and n=36 for the control group). Demographic features, clinical characteristics, IMA, and IMA/albumin levels were compared between the groups. Study group was divided into subgroups based on the number of patches, disease duration, and number of disease attacks. IMA and IMA/albumin levels were compared between each subgroup. Results: Study and control groups were similar with regard to demographic features and clinical characteristics. Significant differences were observed between the mean IMA and IMA /albumin ratio (p=0.004 and 0.012, respectively). The study subgroups were comparable for the number of patches, disease duration and number of disease attack. Conclusion: Although oxydative stress is an important component in the etiology of AA, IMA and IMA/albumin may not be useful in the prediction of disease severity in patients with AA.